EFEKTIFITAS BERMAIN BERJALAN DI ATAS JEJAK KAKI UNTUK MENINGKATKAN KESEIMBANGAN ANAK AUTISME - Yerika - Fauziah (Jurnal Penelitian Pendidikan Khusus, 2012)
Against the background of this research by the problems that researchers in the field is found in an autistic child in the class III in SLB YPPA Bukittinggi. Impaired children in terms of balance runs, but the child is able to stand with your head erect with eyes fixed forward, stand upright posture and stance legs stand straight and stretched by a fist punching the adult but the child had not been able to walk with swing hands as feet. Can be concluded that the play goes on to improve the balance of footprints walking children with autism. Suggested to the principal and the teachers are always looking for the policy to determine all that is good for children with autism included in the balance.